Experimental and Monte Carlo studies of fluence corrections for graphite calorimetry in low‐ and high‐energy clinical proton beams. Issue 7 (13th June 2016) - Lourenço, Ana; Thomas, Russell; Bouchard, Hugo; Kacperek, Andrzej; Vondracek, Vladimir; Royle, Gary; Palmans, Hugo
Abstract : Purpose: The aim of this study was to determine fluence corrections necessary to convert absorbed dose to graphite, measured by graphite calorimetry, to absorbed dose to water. Fluence corrections were obtained from experiments and Monte Carlo simulations in low‐ and high‐energy proton beams. Methods: Fluence corrections were calculated to account for the difference in fluence between water and graphite at equivalent depths. Measurements were performed with narrow proton beams. Plane‐parallel‐plate ionization chambers with a large collecting area compared to the beam diameter were used to intercept the whole beam. High‐ and low‐energy proton beams were provided by a scanning and double scattering delivery system, respectively. A mathematical formalism was established to relate fluence corrections derived from Monte Carlo simulations, using thefluka code [A. Ferrari et al., "fluka : A multi‐particle transport code, " in CERN 2005‐10, INFN/TC 05/11, SLAC‐R‐773 (2005) and T. T. Böhlen et al., "Thefluka Code: Developments and challenges for high energy and medical applications, " Nucl. Data Sheets120, 211–214 (2014)], to partial fluence corrections measured experimentally. Results: A good agreement was found between the partial fluence corrections derived by Monte Carlo simulations and those determined experimentally. For a high‐energy beam of 180 MeV, the fluence corrections from Monte Carlo simulations were found to increase from 0.99 to 1.04 with depth. In the case of a low‐energy beam of 60 MeV, the magnitude of fluence corrections was approximately 0.99 at all depths when calculated in the sensitive area of the chamber used in the experiments. Fluence correction calculations were also performed for a larger area and found to increase from 0.99 at the surface to 1.01 at greater depths. Conclusions: Fluence corrections obtained experimentally are partial fluence corrections because they account for differences in the primary and part of the secondary particle fluence. A correction factor, F ( d ), has been established to relate fluence corrections defined theoretically to partial fluence corrections derived experimentally. The findings presented here are also relevant to water and tissue‐equivalent‐plastic materials given their carbon content.